Strategi Efektif Dalam Mengelola Disiplin Kelas Untuk Meningkatkan Pembelajaran yang Kondusif - Mustikaati, Wina; Fitriyani, Devita; Sari, Tria Kurnia; Iswanti, Renata Dwi; Nuralmira, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Good classroom discipline not only supports the smooth running of the teaching and learning process, but also contributes significantly to the achievement of optimal learning outcomes. The main purpose of creating a quality learning environment is to support learners in developing their full potential. The method used in this research is a qualitative approach using the literature study method. This study examines various similar research findings that explain the problem under study. Effective classroom discipline is based on a positive approach, open communication, clear rules, and proactive strategies. Teachers build positive relationships with students through empathy, constructive feedback, and appreciation of student effort. Positive discipline fosters responsibility, character, and a comfortable learning environment that values students' holistic and sustainable development. Classroom discipline is an important foundation for creating an orderly learning atmosphere and avoiding deviant behavior. Effective discipline approaches must be based on human values and democratic principles, and prioritize non-violent methods such as positive discipline. Overall, the implementation of humanist, democratic and positive discipline can shape students' responsible character and support their academic and social development.